'Indirect amendment': how the federal department of justice unilaterally alters the text of the constitution of Canada. Issue 1 (2nd January 2018) - Bowden, James William John
Abstract : Since 1957, the Department of Justice of Canada has regularly altered the wording of some sections of the Constitution Act, 1867 in its consolidated versions of the Constitution of Canada, even though neither the Westminster Parliament nor the Parliament of Canada had ever amended these provisions themselves or delegated to the executive the authority to make changes on their behalf. The Department of Justice refers to its practice of altering the text of the Constitution of Canada as 'indirect amendment'. However, since the Constitution Act, 1982 states categorically that the Constitution of Canada can only be validly amended through one of its five amending formulas, the Department of Justice's technocratic approach to 'indirect amendment' is almost certainly unconstitutional. Either the Department of Justice should restore the original wording of the text of these sections in its subsequent consolidations of the Constitution Acts and relegate the updated figures or other commentary to explanatory footnotes. Alternatively, the Parliament of Canada should update these sections itself, directly, as a Section 44 Constitutional Amendment. The rule of law depends upon following the Constitution of Canada's amendment procedures properly.